ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL BIRU KELANA KARYA DELLA DARTYAN - Surdani Kanopani Hutagalung; Suhardi; Tessa Dwi Leoni; Ahada Wahyusari; Dody Irawan; Abdul Malik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the character education values found in the novel BiruKelana by Della Dartyan. The research object is the character education valuespresented in the novel. This study uses a descriptive method with a qualitativeapproach. Data collection techniques employed include reduction, interviews, andrecording. Data analysis techniques involve data collection, data presentation, anddrawing conclusions. The analysis revealed that the character education values inBiru Kelana encompass religiousness, honesty, discipline, hard work, creativity,independence, curiosity, nationalism, patriotism, appreciation of achievements,friendliness/communication, love for peace, reading interest, environmental care,social care, and responsibility. Based on the conclusions drawn from the research, itwas determined that the novel Biru kelana by Della Dartyan contains significantcharacter education values.